Presence of Dioctophyme renale in domestic and wild cycles in the Brazilian Cerrado - Assis-silva, Zara Mariana De; Fernandes-silva, Lizandra; Moraes, Iago De Sá; Alves-ribeiro, Bruna Samara; Moraes, Reiner Silveira De [UNESP]; Regalin, Doughlas; Braga, Ísis Assis; Saturnino, Klaus Casaro; Ramos, Dirceu Guilherme De Souza (Colégio Brasileiro de Parasitologia Veterinária, 2025)
Despite several records of Dioctophyme renale in domestic hosts (mainly dogs) and wild animals in Brazil, there are few studies related to the biology of the parasite and epidemiology of the parasitosis in the country. This also applies to the interactions and scratches in different locales. The aim of this study was to describe D. renale occurrence in 12 animals at an interface of the domestic-wild cycle and to detail two specific cases of these, one domestic and one wild canine (Chrysocyon brachyurus) from the same microregion of the Brazilian Cerrado. The difficulty in diagnosing dioctophimosis is related to nonspecific clinical signs. Over the last five years, 12 cases of D. renale have been reported in domestic and wild canids, two of which are described in full in this study. The expansion of livestock farming and urbanization of biomes, fragmentation of floral areas, and destruction of natural areas have increased the proximity between domestic and wild animals, and consequently, the occurrence of infectious and parasitic diseases. Its probability of occurrence in humans represents a public health risk.

Apesar de diversos registros de Dioctophyme renale em hospedeiros domésticos (principalmente cães) e animais silvestres no Brasil, existem poucos estudos sobre a biologia do parasito e a epidemiologia da parasitose no país. Isso também se aplica às interações e variações regionais. O objetivo deste estudo foi descrever a ocorrência de D. renale em 12 animais em uma interface do ciclo doméstico-selvagem e detalhar dois casos específicos destes, um canino doméstico e um selvagem (Chrysocyon brachyurus) da mesma microrregião do Cerrado brasileiro. A dificuldade no diagnóstico da dioctofimose está relacionada aos sinais clínicos inespecíficos. Nos últimos cinco anos, 12 casos de dioctofimose foram relatados em canídeos domésticos e selvagens, dos quais dois são descritos na íntegra neste estudo. A expansão da pecuária e a urbanização dos biomas, a fragmentação das áreas florais e a destruição das áreas naturais aumentaram a proximidade entre os animais domésticos e silvestres e, consequentemente, a ocorrência de doenças infecciosas e parasitárias. Sua probabilidade de ocorrência em humanos representa um risco à saúde pública.
Presença de Dioctophyme renale numa interface doméstico-silvestre no Cerrado brasileiro
Keywords: Canides; fragmentation; micro-region; zoonosis; Canídeos; fragmentação; microrregião; zoonose